Pengaruh Metode Wall Bounce Terhadap Kemampuan Passing Bawah Siswa Ekstrakulikuler Bola Voli Smk Al-Ihya Selajambe - Arip Sutisna (STKIP Muhammadiyah Kuningan, 2022)
Arip Sutisna (NIM: 182223132), The Effect of the Wall Bounce Method on the Lower Passing Ability of Volleyball Extracurricular Students at SMK Al-Ihya Selajambe, Health and Recreation Physical Education Study Program, 2022. The purpose of this study was to determine the bottom passing ability of volleyball extracurricular students at SMK Al-Ihya, Selajambe. This research is a quantitative research with one group pretest and posttest research design. The subjects of this study were students who took part in volleyball extracurricular activities at SMK Al-Ihya Selajambe, with a total of 20 students. The results of the t-test research on improving the ability of passing down obtained t count of 22,100 which is greater than t table of 2,100 with a significance level of 0.000. So there is a significant increase in passing down with the wall bounce method for students who take volleyball extracurricular activities at SMK Al-Ihya Selajambe. The amount of increase from the exercise in the form of the wall bounce method is 44.07% from the average difference between the pretest and the posttest is 22.10, the percentage increase is by dividing the average difference between the pretest average and multiplied by 100%. Keywords: Wall Bounce, Down Passing Ability